Analysis of Entrepreneurship Interest on Business Productivity - Setyawan, Nanang Adie; Wibowo, Bagus Yunianto; Ayuwardani, Mellasanti (Jurnal Sains Sosio Humaniora, 2021)
This study was conducted to determine the interest in entrepreneurship and business productivity of Semarang State Polytechnic students during the covid-19 pandemic. Respondents in this study were Semarang State Polytechnic students who had a business in the middle of their learning on campus totaling 100 students. This study uses confirmatory factor analysis and maximum likelihood estimation techniques on SEM (Structural Equations Modeling) from the AMOS 24.0 statistical package (Analysis of Moment Structure). The data collection technique used a questionnaire with a differential semantic scale. The parameter estimation results are in accordance with the hypothesis that entrepreneurial understanding significantly affects entrepreneurial interest with an estimated standardized coefficient value of 0.534 and P-Value ***, as well as entrepreneurship training has a positive effect on entrepreneurial interest with an estimated standardized coefficient value of 0.503 and P-Value *** and interest in entrepreneurship significantly affects business productivity with an estimated standardized coefficient of 0.361 and P-Value ***. From this research, it can be concluded that in the midst of the current covid-19 pandemic, students who are engaged in the world of entrepreneurship need to increase their training and understanding related to entrepreneurship, especially with the current digitalization era which is growing rapidly, there needs to be innovations that can make them survive in a better direction according to the times.